Should TV Move? - Tanner, Giles; Given, Jock (Journal of Telecommunications and the Digital Economy, 2020)
This article considers five options for the future of television transmission in Australia. We begin by describing the unprecedented threats to broadcast television’s business model and power. We then set out the global picture for terrestrial TV broadcasting and options for modernising the Australian system. We do this within a framework that asks what now constitutes “television”, because the services that viewers and users now treat as TV are broader than the subset that have carried most of the public policy freight for decades. The five options we consider are: first, do nothing much apart from adopting further improvements in compression technology; second, replace the current transmission system with a new, specialised terrestrial broadcast platform; third, migrate terrestrial TV to a direct-to-home satellite platform; fourth, move over-the-air TV online; fifth, design some sort of hybrid of Options 1 to 4. Finally, we arrive at some tentative conclusions.